Function of Theatrical Gesture in Chekhovian Poetics of Negation on the Basis of Selected Short Stories by A.P. Chekhov - Waligorska-Olejniczak, Beata (Institute of Literature Press, Tbilisi, 2011)
19th century was a period of dynamic changes in the field of literature; it was the time which has given rise to the many experiments aimed at defining the role of art. One of the core problems was also the notion of a new, educated recipient who was to understand the meaning of a work and cross its transient boundaries to grasp the metaphysical sense. A. P. Chekhov belonged to the group of 19th century artists who studied the problem of perception and emphasized the importance of intuiti.on and instinct in the process of creation. Being both a physician and an author helped him to master his method of deep realism with its ecological view of the human being focused on the relationship between the physical and spiritual. My paper proposes the interpretation of Chekhov's short stories as the attempt to explore the function of the category of theatrical gesture, which allows us to see his prose of 80s and 90s as the anticipation of Chekhovian poetics of negation exposed in his dramas during the period of the Great Theatre Reform. Theatrical gesture is treated as the peculiar key for decoding the text, the tool that can reveal the role of "the emptiness" In his t.exts. Lotman's notion of the meaningful absence, which is emphasized in the analysis, seems to be an adequatc metaphor exposing the creative exploitation of contrastive elements in his stories, whose interdependence and juxtaposition can create the source of the dynamics of the text, interpenetration of profanum and sacrum.
Keywords: Czechow; Chekhov; gesture; gest; poetyka negacji; negation; meaningful abscence; nieobecność znacząca; corporeality; cielesność; opowiadania Chechowa; short stories by Chekhov